The Influence of The Project-based Learning Model on Students' Critical Thinking Skills in The Science Subject - Gaby M. Manurung; Emelda Thesalonika; Rio P. Napitupulu (International Journal of Contemporary Studies in Education (IJ-CSE), 2026)
Purpose – Critical thinking is a key competency in elementary education, particularly in Natural and Social Sciences (IPAS), yet classroom instruction often emphasizes memorization rather than inquiry and problem solving. This study aimed to examine the effect of the Project-Based Learning (PjBL) model on the critical thinking skills of fifth-grade students. Methodology – This quantitative study employed a one-group pretest-posttest experimental design involving 24 fifth-grade students at State Elementary School 124401 Pematangsiantar. Critical thinking data were collected using an expert-validated essay test. The intervention consisted of IPAS instruction using the PjBL model. Data were analyzed through descriptive statistics and N-gain analysis to measure students' learning improvement. Findings – Students' mean critical thinking score increased from 52.50 in the pretest to 85.33 in the posttest, with an N-gain of 0.70, indicating a high level of improvement. These findings demonstrate that PjBL effectively enhances elementary students' critical thinking skills in IPAS learning. Novelty – This study provides empirical evidence on the effectiveness of PjBL in fostering critical thinking among elementary school students within the context of IPAS instruction. Significance – The findings offer practical guidance for elementary school teachers in selecting student-centered learning approaches and provide evidence for schools and curriculum developers seeking to strengthen higher-order thinking skills through project-based instruction.